Cognitive impairment and clinical characteristics in patients with chronic obstructive pulmonary disease. (May 2018) - Cleutjens, Fiona A H M; Spruit, Martijn A; Ponds, Rudolf W H M; Vanfleteren, Lowie E G W; Franssen, Frits M E; Gijsen, Candy; Dijkstra, Jeanette B; Wouters, Emiel F M; Janssen, Daisy J A
We aimed to investigate (1) the relationship between cognitive impairment (CI) and disease severity and (2) the potential differences in exercise performance, daily activities, health status, and psychological well-being between patients with and without CI. Clinically stable chronic obstructive pulmonary disease (COPD) patients, referred for pulmonary rehabilitation, underwent a neuropsychological examination. Functional exercise capacity (6-minute walk test [6MWT]), daily activities (Canadian Occupational Performance Measure [COPM]), health status (COPD Assessment Test [CAT]) and St George's Respiratory Questionnaire-COPD specific [SGRQ-C]), and psychological well-being (Hospital Anxiety and Depression Scale [HADS], Beck Depression Inventory [BDI], and Symptom Checklist 90 [SCL-90]) were compared between patients with and without CI. Of 183 COPD patients (mean age 63.6 (9.4) years, FEV1 54.8 (23.0%) predicted), 76 (41.5%) patients had CI. The prevalence was comparable across Global Initiative for Chronic Obstructive Lung Disease (GOLD) grades 1–4 (44.8%, 40.0%, 41.0%, 43.5%, respectively, p = 0.97) and GOLD groups A–D (50.0%, 44.7%, 33.3%, 40.2%, respectively, p = 0.91). Patients with and without CI were comparable for demographics, smoking status, FEV1 % predicted, mMRC, 6MWT, COPM, CAT, HADS, BDI, and SCL-90 scores. Clinical characteristics of COPD patients with and without CI are comparable. Assessment of CI in COPD, thus, requires an active case-finding approach.